2013
DOI: 10.1002/jbmr.1989
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-15 Regulates Osteoclast Differentiation by Modulating RANKL-Induced Phosphatidylinositol 3-Kinase/Akt and Erk Pathways in Association With Signaling Adaptor DAP12

Abstract: Siglecs are a family of sialic acid-binding immunoglobulin-like lectins that regulate the functions of cells in the innate and adaptive immune systems through glycan recognition. Here we show that Siglec-15 regulates osteoclast development and bone resorption by modulating receptor activator of nuclear factor kB ligand (RANKL) signaling in association with DNAX-activating protein 12 kDa (DAP12), an adaptor protein bearing an immunoreceptor tyrosine-based activation motif (ITAM). Among the known Siglecs express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 40 publications
(68 reference statements)
8
103
0
Order By: Relevance
“…This could potentially result in a reduction in the rare but devastating side effects of current therapeutics, which include osteonecrosis of the jaw (39), and atypical fractures of the femur (40). Both the specificity of Siglec-15 expression in osteoclasts and the potential for Siglec-15 targeted therapies to preserve osteoblast-osteoclast coupling and bone formation are supported by the mildly osteopetrotic but otherwise normal phenotype of the recently described siglec-15 Ϫ/Ϫ mice (27,28). Although further studies will be helpful to fully characterize their in vivo effects, these characteristics suggest that Siglec-15 antibodies could have distinct advantages over existing drugs, and therefore, we believe that continued development of this novel class of bone loss therapeutic is certainly warranted.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could potentially result in a reduction in the rare but devastating side effects of current therapeutics, which include osteonecrosis of the jaw (39), and atypical fractures of the femur (40). Both the specificity of Siglec-15 expression in osteoclasts and the potential for Siglec-15 targeted therapies to preserve osteoblast-osteoclast coupling and bone formation are supported by the mildly osteopetrotic but otherwise normal phenotype of the recently described siglec-15 Ϫ/Ϫ mice (27,28). Although further studies will be helpful to fully characterize their in vivo effects, these characteristics suggest that Siglec-15 antibodies could have distinct advantages over existing drugs, and therefore, we believe that continued development of this novel class of bone loss therapeutic is certainly warranted.…”
Section: Discussionmentioning
confidence: 95%
“…Very recently, following completion of the current study, two groups have independently generated full-body siglec-15 Ϫ/Ϫ mice (27,28). These mice are viable and healthy and display a mildly osteopetrotic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acid-binding Ig-like lectin (Siglec)-15 is a DAP12-associated immunoreceptor that recognizes sialylated glycans and regulates osteoclast differentiation [11,12]. We previously demonstrated that Siglec-15 is involved in physiologic bone remodeling by modulating RANKL signaling [13].…”
Section: Introductionmentioning
confidence: 99%
“…13) In addition, sugar-binding proteins such as siglec, which interact with sialic acid, and galectins, which interact with Galβ1-4GlcNAc, also have important roles in osteoclastogenesis. [14][15][16][17][18][19] Therefore, in order to clarify the potential for GlcN-mediated glycosylation modification, we investigated the effect of GlcN treatment on the pattern of glycosylation using lectin blotting of cell extracts with SSA, MAM, RCA120, PHA-E 4 , Con A, and LCA, which mainly recognize α2,6-linked sialic acid, α2,3-linked sialic acid, Galβ1-4GlcNAc, bisecting GlcNAc, high mannose type Nglycan, and N-glycan core modified with fucose, respectively (Figs. 2B-G).…”
Section: Glcn Suppresses the Osteoclastic Differentiation Of Raw264 Cmentioning
confidence: 99%